2006
DOI: 10.1002/ffj.1613
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the volatile oils of Satureja spicigera C. Koch Boiss. and S. macrantha C. A. Mey from Iran

Abstract: The essential oils of the aerial parts of Satureja spicigera (C. Koch) Boiss. and S. macrantha C. A. Mey., from Iran, have been analysed by GC and GC-MS. Forty-three compounds in the oil of S. spicigera, representing 97.4% of the total oil, and 48 compounds in the oil of S. macrantha, representing 92.1%, were identified. The oil of S. spicigera was rich in monoterpenes (89.9%) with thymol (37.3%) as the major compound, but the oil of S. Aerial parts of the plants were dried at room temperature, cut into small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Furthermore, a significant amount of sesquiterpene hydrocarbons (11.4%) were found at the flowering stage. Our results were in agreement with previous research where carvacrol, p-cymene, γ-terpinene and thymol were found as the marker volatiles of S. macrantha [14][15][16]. The thymol content was higher at the flowering stage compared to the other two stages.…”
Section: Essential Oil Analysissupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, a significant amount of sesquiterpene hydrocarbons (11.4%) were found at the flowering stage. Our results were in agreement with previous research where carvacrol, p-cymene, γ-terpinene and thymol were found as the marker volatiles of S. macrantha [14][15][16]. The thymol content was higher at the flowering stage compared to the other two stages.…”
Section: Essential Oil Analysissupporting
confidence: 93%
“…The highest EO yield was recorded at the flowering stage (1.8%) while the lowest content was observed at the fruiting stage (1.4%). The yield values observed in the present study were comparable to those previously reported by Sefidkon and Jamzad [14] and Gohari et al [16], who found values ranging from 0.30% to 1.48%. The highest EO yield at the flowering stage is a usual phenomenon observed in many MAPs, in particular with those belonging to the Lamiaceae family [34,35].…”
Section: Essential Oil Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, its leaf part is used as food flavoring [8]. In the literature, there are several studies on its essential oil content and biological activities [8][9][10][11]. However, this is the first study on the chemical contents and biological activities of the ethanol extract of S. macrantha, and also on the cultivated S. macrantha.…”
Section: Introductionmentioning
confidence: 98%
“…[123] Essential oils of these plants consist of various monoterpenes and sesquiterpenes, as well as their derivatives, such as alcohols, aldehydes, esters, and acetates. [456] Terpenoids are formed from the condensation of dimethylallyl pyrophosphate (DMAPP) and isopentyl pyrophosphate (IPP), to give geranyl diphosphate (GPP), farnesyl diphosphate (FPP), or geranyl geranyl diphosphate (GGPP). [789] Terpene synthases in plant kingdom may fall into two categories.…”
Section: Introductionmentioning
confidence: 99%